Potentiometric studies of mixed complexes of Cobalt(II) and Copper(II) with L-asparagine and adenine - CÜCÜ, AYŞEN (Gordon and Breach Science Publishers, 1999)
A potentiometric titration technique has been used to determine the stability constants for the various complexes of Co(II) and Cu(II) with L-asparagine and from DNA base, e.g. adenine. Stability constants of ternary systems have been evaluated by the method suggested by Irwing-Rossotti. In addition, the conditional constants were calculated as a function of pH. The maximum values of the conditional formation constants were found to be in accordance with the mixed-ligand complex formation constants in a determined pH region. Furthermore, the molar fractions of different species from mixed complexes were calculated by means of formation constants. The values of stability constants of mixed-ligand complexes at 25°C are as follows: log K = 5.25 for Co(II)-L-asparagine-adenine; log K = 9.30 for Cu(II)-L-asparagine-adenine. The ionic strength was kept constant at I = 0.20 with NaClO4.
Keywords: Adenin; Cobalt(II) and Copper(II) complexes; L-asparagine; Mixed complexes; Stability constants